2014
DOI: 10.1002/tesj.158
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Misconceptions About Nonnative English Speakers in the TESOL (NNEST) Movement

Abstract: Parallel to the growing recognition of English as an international language, the fundamental premises of the TESOL discipline (e.g., the ownership of the language, native speakers as a goal and model of competence for learning and teaching, linguistic standards and language variety/ies to be taught, monolingual/monocultural approach to teaching) has undergone a serious challenge and reconceptualization over the past several decades. While this trend resulted in an unprecedented recognition of the issues surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 74 publications
(106 reference statements)
0
84
0
Order By: Relevance
“…However, it is important to note that students’ preference and attitude toward teachers could be a multifaceted phenomenon, as it can be affected by a range of factors especially related to teachers’ level of professionalism despite their L1 background and physical appearance (Selvi, ). For example, Moussu's () study revealed that students’ impressions of their LX user EFL teachers became more positive over the semester.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is important to note that students’ preference and attitude toward teachers could be a multifaceted phenomenon, as it can be affected by a range of factors especially related to teachers’ level of professionalism despite their L1 background and physical appearance (Selvi, ). For example, Moussu's () study revealed that students’ impressions of their LX user EFL teachers became more positive over the semester.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two years later, in 2008, the organization upgraded the NNEST Caucus to an Interest Section, thus giving it improved status and enhanced visibility. (See Selvi, , for a detailed essay on the NNEST movement. )…”
Section: The Marginality Of the Majoritymentioning
confidence: 99%
“…Together, these three points reinforce the notion evident from moments 1 and 2 that people from a given nation are expected to look, speak, and act in certain ways similar to one another and emblematic of that nation, and that those who deviate from these expectations are somehow inferior or illegitimate. Finally, unearthing the historical roots of such mechanisms of (non) native speakering sheds light on why asserting the "privilege" of nonnative speakers" (Medgyes, 1992;Selvi, 2014) in some ways undermines the very equity it attempts to advance-such an effort it itself constructs a nonnative speakered subject, which is inherently inferior to its simultaneously produced native speakered counterpart.…”
Section: Historicizing (Non)native Speakeringmentioning
confidence: 98%
“…The movement has explored the impact of these native speaker ideologies on the lived experiences and identity development of NNESTs around the world (e.g., Amin, 1997;Brutt-Griffler & Samimy, 2001;Reves & Medgyes, 1994;Park, 2012;Rudolph, 2012;Tang, 1997). From this perspective, foundational concepts in language acquisition such as fossilization (Selinker, 1972), ideal language input (Long, 1981), and target language norms (Ellis, 1994), that form the "bedrock of transnationalized ELT" (Leung, 2005, p. 128) not only perpetuate the notion of the existence of an "idealized native speaker-listener" (Chomsky, 1965, p. 3) and "ideal" or "target" language features but also risk obscuring the dynamic nature of language development, assume languages and native speakers are internally homogeneous, and marginalize those who speak lessprivileged language varieties (Selvi, 2014).…”
Section: Brief Overview Of the Nnest Movementmentioning
confidence: 98%